(untitled) (AYUSHDHARA, 2022)
Urinary disorders have been vividly described in Ayurveda. Mutraroga are classified as Mutra-Apravrtijanya and Mutra-Atipravrtijanya Roga in Ashtanga Hridya Nidana. Mutrakrichhra and Mutraghata are two main diseases which are included under the Mutra-Apravrtijanya disorders. Mutraghata means the Alpapravriti of urine where as Mutrakrichhra seems to be due to the painful process of micturition. The disease Pittaja Mutrakrichhra was well acknowledged in Samhitas with different treatment modalities, which can be concurrent to urinary tract infections on theoretical and clinical symptomatology of disease. Eight types of Mutrakrichhra are described in details in Madhav Nidana- i.e., Vattaja, Pittaja, Kaphaja, Sannipataja, Shalyaja, Ashmrija, Shukraja, Purishaja Mutrakrichhra. All the Nidana of Mutrakrichhra ultimately results in the Tridosha prokopa and Mandagni (Aam production) which along with Kha Vaigunya initiates further pathogenesis and its features are Sadaha Mutrata, Peeta Mutrata, Sarakta Mutrata, Krichhra Mutrata, Saruja Mutrata and Muhur muhur Mutrata. This purpose of the article is to understand the modern concept of Urinary tract infections with Ayurvedic concept of Pittaja Mutrakrichhra